Impacts of habitat modification on the dynamics of waterbird diversity in Guangzhou Haizhu National Wetland Park - Chen, Zhouhan; Fang, Xiaoshan; Lin, Shangjiangfeng; Zhang, Xuefei; Yu, Dongmei; Liu, Yuanzhihong; Liu, Xiqing; Hu, Huijian (Global ecology and conservation, 2025)
The Pearl River Delta (PRD) is a crucial habitat for over 120 species of waterbirds, including migratory species. As a key component of the wetland resources in the PRD, Guangzhou Haizhu National Wetland Park (GHNWP) plays a vital role in supporting the waterbird ecological corridor along the East Asia-Australasia Flyway. Since 2013, GHNWP has been engaged in ecological restoration aimed at enhancing waterbird diversity, which has attracted widespread attention. By 2022, significant changes in habitat structure had occurred, making it an important site for waterbird aggregation. This study, based on waterbird survey data from 2013 to 2022, employed Spearman’s correlation coefficient and regression analysis to assess the impact of long-term habitat modification on the dynamic changes in waterbird diversity. The results indicated that habitat modifications significantly increased waterbird abundance, richness, and the Shannon-Wiener diversity index, with these changes closely related to habitat modifications. Further regression analysis revealed that waterbird richness and Shannon-Wiener diversity index were significantly influenced by the area-weighted mean shape index (AWMSI), and the Pielou’s evenness index was significantly affected by the area of paddy fields. Additionally, the study quantified the relationships between these factors and changes in waterbird diversity. The finding contributes to a better understanding of how waterbird diversity responds to long-term habitat changes and provides effective management recommendations and solutions for waterbird conservation and habitat restoration in urban wetlands.